Documenting Information Processes and Practices: Paradata, Provenance Metadata, Life‐Cycles and Pipelines. Issue 1 (13th October 2021) - Huvila, Isto; Greenberg, Jane; Sköld, Olle; Thomer, Andrea; Trace, Ciaran; Zhao, Xintong
Abstract: Processes and practices—and in general, informational doings and their diverse constellations—are pertinent elements of the information landscape. This panel presents research on documentation and description of processes and practices in the information field addressing: 1) how different conceptualisations of processes and practices influence how they emerge as describable entities; 2) what different approaches to document and describe processes and practices exist and have been proposed in information science and technology research; 3) what aspects of processes and practices different documentation approaches capture, make visible and invisible; and 4) what novel insights from the current state‐of‐the‐art research can be drawn to support practitioners in different areas of the information field, including knowledge organisation, information management, information literacy instruction, and development of information systems and services.